Pre-service Biology Teachers’ Use of Science Process Skills in the Context of a STEM Acitivity; Nano Pharmaceuticals - Göktaş, Anıl (GLOBETS 2023 Educational Technology and Science Research, 2024)
Science process skills are defined as the most powerful tool for acquiring information about the world and organizing this knowledge. When literature is examined, it is evident that teachers and pre-service teachers in various disciplines lack sufficient science process skills. The periods during which individuals can gain nanotechnology literacy, especially in their formal education years, increase the importance of teachers’ and pre-service teachers’ knowledge and skills in these areas. The aim of this study is to determine the instances of pre-service biology teachers utilizing science process skills within the scope of the 'Nano-Drug STEM Activity.' For this purpose, the researcher implemented an activity using commercially available materials that serve as an example of understanding nanotechnology science and its practical applications in contemporary life. The participants in the study were 4th-year pre-service biology teachers (9 individuals). Within the application, teacher candidates were divided into groups of three, and collaborative learning approaches were employed to conduct the activities. In this study, the responses written by the participants on the worksheets they worked on during the application were analyzed. Two external researchers' opinions were obtained during the analysis process to assess the participants' utilization of science process skills. Upon analyzing the data, shortcomings were identified in the science process skills of biology teacher candidates, particularly in hypothesis formulation, identifying relevant data, determining dependent and independent variables in the activity, and writing results consistent with the research question.